Cowpea as a key factor for a new approach to integrated crop-livestock systems research in the dry savannas of West Africa - Tarawali, Shirley A.; Singh, B.B.; Gupta, S.C.; Tabo, Ramadjita; Harris, F.; Nokoe, S.; Fernández Rivera, S.; Bationo, B. André; Manyong, Victor M.; Makinde, K.; Odion, E.C. (International Institute of Tropical Agriculture, 2002)
Agriculture in the dry savannas is intensifying in response to increasing populations of humans and livestock. As a result, increased productivity demands are placed upon integrated crop-livestock systems and more emphasis is on the roles of legumes such as cowpea. Cowpea has the potential to function as a key integrating factor in intensifying systems through supplying protein in the human diet, and fodder for livestock, and bringing nitrogen into the farming system through nitrogen fixation. This paper describes the Development and evaluation of integrated "best-bet" options which maximize the benefits of cowpea and addresses aspects of improved crop varieties, crop and livestock management, nutrient cycling, and soil fertility. The approach used includes a multi center, multidisciplinary approach to working with farmers which combines complementary strengths of previous component research involving crops and livestock by key international and national research institutions in the region.